FEATURES OF CEREBRAL HEMODYNAMICS IN ELDERLY PATIENTS WITH TRANSIENT ISCHEMIC ATTACKS - M.A. Bakhadirova; S.Yu. Isamukhame¬dova (International Scientific and Current Research Conferences, 2025)
Transient ischemic attacks (TIAs) are acute cerebrovascular events characterized by temporary neurological dysfunction resulting from focal cerebral ischemia. Elderly patients represent a particularly vulnerable population due to age-related changes in vascular structure and cerebral autoregulation. This article discusses the pathophysiological characteristics of cerebral hemodynamics in elderly individuals with TIAs, evaluates diagnostic approaches, and highlights the implications for early intervention and stroke prevention.